2018
DOI: 10.1088/1361-6641/aabc6f
|View full text |Cite
|
Sign up to set email alerts
|

Temperature controlled properties of sub-micron thin SnS films

Abstract: Tin sulphide (SnS) thin films deposited by thermal evaporation on glass substrates are studied for different substrate temperatures. The increase in substrate temperature results in the increase of the crystallite size and change in orientation of the films. The crystal structure of the film is that of SnS only and for temperatures  300 o C the films are of random orientation, whereas for higher temperatures the films become (040) oriented. The variation of Sn/S composition was accompanied by a reduction in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…From Table 1, one can deduce that the band gap increases with deposition cycles, which indicates that the band gaps are highly dependent on the deposition cycles. The band gap values showed that PbSnS is a ternary material whose band gap system falls between the range of the 2 binary constituents of SnS (1.0-1.47 eV) [6,7] and PbS (2.1-2.75 eV) [21,22]. Increasing the deposition cycles shift the bandgap value of the ternary PbSnS material till it reaches 1.75 eV, dueto the gradual replacement of some Sn atoms by Pb atoms in the ternary PbSnS matrix.…”
Section: Optical Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…From Table 1, one can deduce that the band gap increases with deposition cycles, which indicates that the band gaps are highly dependent on the deposition cycles. The band gap values showed that PbSnS is a ternary material whose band gap system falls between the range of the 2 binary constituents of SnS (1.0-1.47 eV) [6,7] and PbS (2.1-2.75 eV) [21,22]. Increasing the deposition cycles shift the bandgap value of the ternary PbSnS material till it reaches 1.75 eV, dueto the gradual replacement of some Sn atoms by Pb atoms in the ternary PbSnS matrix.…”
Section: Optical Studiesmentioning
confidence: 99%
“…Thin films of SnS are suitable for various devices such as photo-detectors, infrared detectors, sensing devices and solar cells fabrication [5]. It is an ideal candidate for making costeffective solar cells having exhibited good optical properties, excellent band gap range of 1.3 to 1.5 eV, high absorption coefficient (~10 5 cm -1 ), good carrier concentrations and hole mobility (0.8 -15.3 cm 2 V -1 S -1 ) [6][7][8]. Besides these properties, theoretical calculations have indicated a realistic conversion efficiency of above 25 % for SnS-based heterojunction solar cells [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tin sulphide (SnS) is a potential material for the production of thin solar cells because of its high absorption coefficient ( α ≈ 10 4 cm −1 near the fundamental edge), suitable band gap ( E g = 1.1-2.1 eV) and high hole mobility of 90 cm 3 V −1 S −1 [1][2][3]. SnS semiconductors could present p or n-type conductivity owing to the preparation conditions and doping materials, which allow the films to be used as an absorption layers in hetero-junction solar cells fabrication [1,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there is no previous literature reported on PVA capped SnS thin films deposited by chemical bath deposition. Table 1 shows the reported literature [11,[47][48][49][50][51][52][53][54] on SnS thin films deposited using different methods. A critical analysis of the literature indicated that deposition of SnS films in all the methods, except CBD was carried out at high temperatures.…”
Section: Introductionmentioning
confidence: 99%